Self-management develops through doing of everyday activities—a longitudinal qualitative study of stroke survivors during two years post-stroke. Issue 1 (December 2016) - Satink, Ton; Josephsson, Staffan; Zajec, Jana; Cup, Edith; de Swart, Bert; Nijhuis-van der Sanden, Maria
Abstract Background A description of the complexity of the process of self-management and the way stroke survivors give meaning to their process of self-management post-stroke is lacking. This study explores how stroke survivors managed their lives, gave meaning to their self-management post-stroke and how this evolved over time. Methods Data was generated through participant observations and interviews of 10 stroke survivors at their homes at 3, 6, 9, 15 and 21 months post-discharge. A constant comparative method was chosen to analyse the data. Results ' Situated doing' was central in stroke survivors' simultaneous development of self-management and their sense of being in charge of everyday life post-stroke. Doing everyday activities provided the stroke survivors with an arena to explore, experience, evaluate, develop and adapt self-management and being in charge of everyday activities and daily life. The influence of stroke survivors' partners on this development was sometimes experienced as empowering and at other times as constraining. Over time, the meaning of self-management and being in charge changed from the opinion that self-management was doing everything yourself towards self-managing and being in charge, if necessary, with the help of others. Moreover, the sense of self-management and being in charge differed among participants: it ranged from managing only at the level of everyday activities to full role management and experiencing a meaningful and valuable life post-stroke. Conclusions The findings of this study indicate the doing of activities as an important arena in which to develop self-management and being in charge post-stroke. Stroke self-management programs could best be delivered in stroke survivors' own environment and focus on not only stroke survivors but also their relatives. Furthermore, the focus of such interventions should be on not only the level of activities but also the existential level of self-management post-stroke.